2018
DOI: 10.1515/rams-2018-0036
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Mechanical and Tribological Properties of Graphite Reinforced Self Lubricating Hybrid Metal Matrix Composites

Abstract: Hybrid metal matrix composites (HMMC’s) are next generation metal matrix composite materials that have the potential of gratifying recent demands of advanced energy applications in the field of aerospace, automobile and biomedical. The MMC’s have to work at elevated temperature or vacuum environment where lubrication using liquid lubricants is ineffective or difficult to achieve; moreover, liquid lubricants are not environmental friendly, since they releases pollutants into environment. Solid lubricants such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The hexagonal structure limits easy dislocation motion to the close-packed direction on the basal planes, and plastic deformation of the hexagonal lattice is more complicated than in cubic latticed metals like aluminum, copper and steel. A material model for magnesium alloys should be able to describe these anisotropy, asymmetry and temperature-dependent behaviors [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hexagonal structure limits easy dislocation motion to the close-packed direction on the basal planes, and plastic deformation of the hexagonal lattice is more complicated than in cubic latticed metals like aluminum, copper and steel. A material model for magnesium alloys should be able to describe these anisotropy, asymmetry and temperature-dependent behaviors [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prakash et al [33] reported that Mg-SiC-Gr hybrid composite possesses three times better microhardness and an approximately 80% less wear rate than the base matrix. Khatkar et al [34] have reviewed the effect of hybridization and reported that graphite possesses noticeable quality as a secondary reinforcement to control mechanical and tribological characteristics. It was also observed that this positive impact of incorporating graphite is obtained up to a transition limit.…”
Section: Introductionmentioning
confidence: 99%
“…Porous iron-based slide bearings are being produced as pure iron bearings without any additions, with a small graphite addition (0.4–1.0% or 0.5–2% of C), and with considerable copper content (1–5% or even 15–25% Cu) with or without graphite. There are also iron bearings being made with up to 3.5% lead added, depending on the application and needs, as well as iron bearings with added manganese, silicon, tin, nickel, or molybdenum disulfide [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%